1987
DOI: 10.1364/josaa.4.001535
|View full text |Cite
|
Sign up to set email alerts
|

Two-dot vernier discrimination within 20 degrees of the foveal center

Abstract: Vernier acuity (delta v) as a function of two-dot separation (s) was measured at five retinal locations between the foveal center and 2.0 deg of eccentricity. We compare these results with average cone spacing at each of the corresponding retinal eccentricities and find that the angular dot separations at which the delta v versus s function intersects the angular cone spacing at each eccentricity remain nearly constant. Further, we define a vernier Weber fraction delta v/s and find that the average Weber fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
1
4
0
1
Order By: Relevance
“…Using a criterion of 65% correct, appropriate for the test luminance used in these experiments [42,50], PG's threshold measured at 100% contrast is approximately 7 sec of arc. This estimate is within the foveal hyperacuity range and in satisfactory agreement with threshold estimates reported in the literature for 2-dot stimuli [30][31][32].…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Using a criterion of 65% correct, appropriate for the test luminance used in these experiments [42,50], PG's threshold measured at 100% contrast is approximately 7 sec of arc. This estimate is within the foveal hyperacuity range and in satisfactory agreement with threshold estimates reported in the literature for 2-dot stimuli [30][31][32].…”
Section: Resultssupporting
confidence: 90%
“…Diffraction limitations of the pupil and image blurring due to the optics of the human eye [28] prevent the illumination of single cones in the center of the fovea where the cone-cone separation is estimated to be approximately 30 sec of arc [3,5,29]. To circumvent this obstacle a hyperacuity paradigm was used to take advantage of the fact that foveal hyperacuity thresholds are significantly smaller than the diameter of a single foveal cone [30][31][32]. Under the expectation that the contribution of a single foveal cone may have measurable effects on hyperacuity performance, comparisons of hyperacuity performance based on the full cone mosaic and on selected submosaics were used to reveal the placement of individual cones in the densely packed photoreceptor array of central fovea.…”
Section: General Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the spatial resolution of a perceived image is highest in the fovea while it is lower in the peripheral visual fields. Groll and Hirsch [1987] reported that the field of view of the fovea with the highest spatial sensitivity corresponds to four degrees. Virsu and Rovamo [1979], on the other hand, measured the contrast sensitivity for discriminating the direction of movent or orientation of sinusoidal gratings both in central and peripheral vision.…”
Section: Introductionmentioning
confidence: 99%
“…No esquema montado na figura 1.3 podemos perceber uma diferença no espaçamento dos cones no centro da fóvea e a 1°de excentricidade ou 60 minutos de arco (arcmin) (Hirsch e Miller, 1987;Groll e Hirsch, 1987 (Regan, 1989;Curcio e Allen, 1990 Os neurônios com oponências de cores são os mais comuns, cerca de 80% do total da camada P. Para uma pequena parte das células P, de 15 a 20%, falta uma sensibilidade bem definida para cores e apresentam uma sensibilidade de uma banda ampla de comprimento de onda (Shapley e Perry, 1986;Regan, 1989;Lee, 1993).…”
Section: Sobre a Retinaunclassified